Device-Measured Physical Activity and Cognitive Processing Speed Impairment in a Large Sample of Persons with Multiple Sclerosis. (25th September 2020) - Sandroff, Brian M.; Motl, Robert W.
Abstract: Objective: There is accumulating evidence regarding the beneficial effects of physical activity (PA) on cognitive processing speed in persons with multiple sclerosis (MS). However, one overarching limitation of this research is that researchers have not recruited samples who have the actual problem of being studied (i.e., cognitive processing speed impairment). This study examined associations between device-measured PA and cognitive processing speed in a large sample of persons with MS overall and between those with and without cognitive processing speed impairment. Method: Three hundred eighty-five persons with MS underwent the oral Symbol Digit Modalities Test (SDMT) and wore an accelerometer for 7 days for PA measurement. We divided the overall sample into subsamples with ( n = 140) and without ( n = 245) cognitive processing speed impairment based on age, sex, and education-adjusted SDMT Z -scores. Results: After controlling for age and disability status, higher levels of device-measured PA were significantly associated with faster cognitive processing speed overall, and the association was significantly stronger among persons with MS who presented with cognitive processing speed impairment. Conclusions: This examination provides initial cross-sectional support for informing the development of PA interventions as a possible approach for managing MS-related cognitive processing speed impairment. This highlights the importance of developing purposefully designed trials involving PA interventions for targeting cognitive processing speed as a primary end point among persons with MS with impaired cognitive processing speed.